Pengaruh Tingkat Pengungkapan Corporate Social Responsibility Terhadap Information Asymmetry dengan Variabel Kontrol Likuiditas dan Kepemilikan Institusional - Hans William Santoso; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
The affect of Corporate Social Responsibility on financial performance had been studied before. However, there were only a few studies about the affect of Corporate Social Responsiblity on Information Asymmetry.This study aims to identify and prove the effect of Corporate Social Responsiblity disclosure to Information Asymmetry.          The Disclosure of Corporate Social Responsbility of company measured using Level Disclosure of Corporate Social Responsiblity that assessed using the criteria of the GRI. Information Asymmetry measured using Bid-ask spread. This research also used control variables that are Liquidity and Institutional Ownership. This research was carried out on public company in Indonesia which publishes sustainability report with sample of 131 observations.          The results showed that there was a significant positive correlation between the disclosure of Corporate Social Responsibility with Information Asymmetry which is measured using bid-ask spread. The results also showed that Liquidity had negative correlation with Information Asymmetry which is measured using bid-ask spread and Institutional Ownership did not affect Information Asymmetry which is measured using bid-ask spread.